2471. The State of Cost-Utility Analyses in Vaccines: A Systematic Review. (26th November 2018) - Lee, Jason; Lu, Patricia; Lam, Gary; Shin, Thomas; Chit, Ayman
Abstract: Background: Economic evaluations are a major consideration of public health decisions on vaccine programs. Given the growth in the number of published cost-utility analyses of vaccines, we sought to better understand global trends in these studies by describing trends in growth, quality, and study findings in the published literature over time. Methods: We reviewed published economic evaluation of vaccines using the Tufts CEA Registry, a comprehensive database of 5, 546 published healthcare related cost-utility analyses. Descriptive data from eligible publications were screened and summarized by reviewers, who also perform an assessment of the quality of each study. We described studied vaccines, their geographic distribution, author affiliation, funding sources, quality and results. Results: There were 379/5, 546 articles examining the cost-effectiveness of vaccines published in the CEA registry between 1980 and 2017. The United States ( n = 121), Canada ( n = 36), the Netherlands (30), and the UK ( n = 29) were the largest publishers, accounting for 57% of total publications. Overall, publications covered 12 therapeutic categories of vaccines, with HPV vaccine-related articles accounting for the largest proportion of articles (25%; n = 94). While the majority of study authors reported academic affiliations ( n = 300), most studies were funded by industry ( n = 120) and government ( n = 94). Most studies reported favorable findings, and 16% of articles ( n = 60) reported cost-savings against comparator interventions. The median ICER of all vaccine cost-effectiveness analyses was approximately $22, 182 USD/quality-adjusted life year. The mean quality rating of all vaccine articles was 4.7/7, and was consistent across funding sources and vaccine type. Conclusion: The publication of cost-utility analyses of vaccines has steadily increased over time. Given the impact of these studies on clinical practice and public health policy, more trained researchers and peer-review processes are needed to utilize this information, especially in jurisdictions that do not have a formal health technology assessment process for vaccines. This study is funded by Sanofi Pasteur. Disclosures: All Authors: Sanofi Pasteur: Employee, Salary.